Assesment of an intervention to reduce the impact of stigma on people with HIV, enabling them to cope with it - Fuster-RuizdeApodaca, Maria J.; Molero, Fernando; Ubillos, Silvia (Anales de Psicología / Annals of Psychology, 2015)
The goal of this study was to assess an intervention program to reduce the impact of stigma on people with HIV and to enable them to cope with it. A quasi-experimental design, with non-equivalent control group and pre-and posttest was used. Participants were 221 people with HIV. of whom 164 received the intervention and 56 made up the non-equivalent control groups. The dependent variables were perception of stigma -enacted and internalized-, self-esteem, perception of self-efficacy, strategies used to cope with stigma -primary control, secondary control, and avoidance- and quality of life. Analysis of variance (MANOVAS and ANOVAS) was conducted to determine pretest differences and differential scores in both groups, and analysis of covariance (MANCOVAS and ANCOVAS) was performed to assess the efficacy of the program. The results showed reduction of perceived stigma and avoidance strategies and an increase in perceived self-efficacy to cope with stigma, disposition to use approach strategies, self-esteem, and quality of life. These results indicate that is possible to train people with HIV to cope with stigma.